Azide-Triggered Bicyclization of o-Alkynylisocyanobenzenes: Synthesis of Tetrazolo[1,5-a]quinolines - Onnicha Khaikate (2020)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim An efficient and rapid synthetic approach for the synthesis of tetrazolo[1,5-a]quinolines has been developed employing the reaction of o-alkynylisocyanobenzenes with sodium azide. The present strategy involved nucleophilic addition of azide to isocyanide followed by 6-endo cyclization. The reaction gives access to a collection of tetrazolo[1,5-a]quinolines with broad functional group in moderate to high yields under metal-, and base-free conditions.